Crossing curricular boundaries for powerful knowledge. Issue 2 (8th August 2020) - Niemelä, Mikko A.
Abstract : This paper makes a theoretical contribution to the discussion of powerful knowledge in education. The major claim is that curriculum integration can structure knowledge for a coherent curriculum and thus, support the idea of powerful knowledge. The mainstream understanding of curriculum integration promotes it as a pedagogical arrangement and views school subjects as being guilty of fragmenting students' experience. Leaning on empirical evidence, this paper argues that the question of integration cannot be left to teachers and students alone; rather, it is crucial to design a coherent written curriculum that supports the teaching‐studying‐learning process with an appropriately differentiated and integrated structure for school subjects. Alternatives for subject design and knowledge‐based curriculum integration with the potential for developing powerful knowledge are presented.